Management of an intrapleural foreign body and empyema with video-assisted thoracoscopy - Ekeke, Chigozirim; Noble, Stephen; Merritt, Robert E. (Journal of Thoracic Disease, 2016)
Intrapleural foreign bodies are rare and there are few reports on the occurrence and management of this uncommon clinical presentation. We report a case of a patient with a history of ingesting multiple foreign bodies, which resulted in multiple laparotomy procedures for extraction. The patient recently required surgical removal of innumerable ingested foreign bodies from the stomach and developed a left empyema post-operatively. Subsequent imaging studies revealed evidence of a foreign object in the left pleural space without evidence of an esophageal perforation or diaphragm injury.